ANALYSIS OF TEACHER'S SPEECH FUNCTION IN ENGLISH LANGUAGE TEACHING AND LEARNING - Elismawati, Elismawati; Hadeli, Hadeli; Arwemi, Arwemi; Fitri, Melviola (Universitas PGRI Sumatera Barat, 2022)
This study deals with the utterances of an English teacher of MA Tarbiyatul Banin, Pati, Jawa Tengah. It is aimed to know the type of speech function used by the English teacher in the classroom and to find out how speech functions are applied by an English teacher in the classroom. Researchers apply a qualitative approach and design content analysis based on Ary et al (2010). The subject of this research was an English teacher in Tarbiyatul Banin, Pati, Jawa Tengah. The source of the data is the entity from whom the data was obtained, and the data is the expression used by the English teacher. The Researchers used audiovisual material for collecting data. The data of transcription are classified into six basic types of speech function; they are expressive, directive, referential, metalinguistic, poetic, and phatic. From the teacher who was observed, the researchers found a different total of utterances from each meeting. The total utterance is 154 utterances which are classified into five types of speech function. How the speech functions are applied by the English teacher in the classroom is when the teacher interacted with her students.